Martin Scorsese's Divine Comedy Movies and Religion - O'Brien, Catherine (Bloomsbury Academic, 2018)
Catherine O'Brien draws on the structure of Dante's Divine Comedy to explore Scorsese's feature films from Who's that knocking at my door (1967-69) to Silence (2016). In Dante's poem in 100 cantos, the Pilgrim is guided by the poet Virgil down through the circles of Hell in Inferno; he then climbs the steep Mountain of the Seven Deadly Sins in Purgatory; and he finally encounters God in Paradise. Embracing this popular analogy, this study envisions Martin Scorsese as a contemporary Dante, with his filmic oeuvre offering the dimensions of a cinematic Divine Comedy. Martin Scorsese's Divine Comedy is the first full-length study to focus on the trajectory of faith and doubt from 1967-2016, taking very seriously the oft-quoted words of the director himself: 'My whole life has been movies and religion. That's it. Nothing else.' Films discussed include GoodFellas, Casino, Taxi Driver and Mean Streets, as well as the more recent Wolf of Wall Street and Silence.